Sustainability Awareness and Behavior of Management Accounting Students: Basis for Course Activity Development - Dela Cruz, John Jay; Foronda, Leanne Joy; Lucas, Mary Grace; Mabborang, Kamilah Mae; Sisperez, Auguste Anthony; Catacutan, Karen Joy (Journal of Governance Risk Management Compliance and Sustainability, 2024)
Sustainability refers to both the planet’s health and humanity’s future well-being, encompassing actions humans take to prevent the depletion of natural resources. Education for Sustainable Development (ESD) plays a vital role in course curricula by helping students develop critical thinking, decision-making, socio-emotional, and behavioral skills. This study examined the awareness and behavior of BS Management Accounting (BSMA) students regarding the three pillars of sustainability as well as the relationship between sustainability education and their awareness and behavior. Using the Knowledge-Attitudes-Practices (KAP) and Knowledge-Attitude-Behavior (KAB) frameworks, this quantitative descriptive research collected data from 349 out of 399 BSMA students (87.47% participation rate) enrolled during SY 2023–2024 at the University of Saint Louis, Northern Philippines. The results revealed that students were generally aware of sustainability and exhibited positive attitudes toward sustainable practices. Enrollment in the SASA 1013 course significantly increased sustainability awareness, but neither year level nor course enrollment had a significant impact on actual sustainability behavior. This study offers insights into the relationship between students’ sustainability awareness and their behavior across the three sustainability pillars. The novelty of this research lies in its focus on BSMA students and the specific role of the SASA 1013 course in fostering sustainability awareness. The study concludes with recommendations for curriculum development and policy initiatives to further promote students’ long-term sustainability awareness and behavior.